2008
DOI: 10.4315/0362-028x-71.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Salmonella Contamination of Raw Shell Eggs Used in Food Service Premises in the United Kingdom, 2005 through 2006

Abstract: This survey was launched after an unusual number of Salmonella Enteritidis outbreaks associated with the use of eggs in food service premises in England and Wales. Between November 2005 and December 2006, 9,528 eggs (1,588 pooled samples of 6 eggs) were collected from 1,567 food service premises in the United Kingdom, most of which (89%) were produced in the United Kingdom. Salmonella was isolated from 6 (0.38%) pools of eggs. Of these, 5 (0.31%) were Salmonella Enteritidis, which were further characterized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…Salmonella was detected in 5.5% of eggs imported from Spain, in 6.3% of eggs of unknown origin, and in 1.1% of eggs imported from the UK. Salmonella was not detected in eggs from other countries (France, Germany, Portugal, USA: 0%) [29,30]. Based on the results of the questionnaire, one-third of the consumers practiced eating raw eggs for medicinal values; this could have some negative effects on health.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella was detected in 5.5% of eggs imported from Spain, in 6.3% of eggs of unknown origin, and in 1.1% of eggs imported from the UK. Salmonella was not detected in eggs from other countries (France, Germany, Portugal, USA: 0%) [29,30]. Based on the results of the questionnaire, one-third of the consumers practiced eating raw eggs for medicinal values; this could have some negative effects on health.…”
Section: Discussionmentioning
confidence: 99%
“…Poultry is considered the single largest reservoir of S. Enteritidis and most risk attribution studies have identified poultry and poultry products as the major source of human infection. S. Enteritidis is passed to humans mainly via handling and consumption of contaminated poultry meat and eggs (De Buck et al, 2004;Kimura et al, 2004;Little et al, 2008;Marcus et al, 2004;Patrick et al, 2004;Snow et al, 2007). For instance, eggs and egg-containing products were implicated as primary vehicles of S. Enteritidis Abbreviations: MLVA, multi-locus variable-number tandem repeat analysis; PI, post-infection; SPI, Salmonella pathogenicity island; TEM, transmission electron microscopy; TTSS, type III secretion system.…”
Section: Introductionmentioning
confidence: 99%
“…Eggshell contamination occurs more frequently than the contamination of the egg contents Davies and Breslin, 2004;Little et al, 2007b;Little et al, 2008). There is a non-linear (quadratic) relationship between infection prevalence in laying hens and the rate of eggshell contamination but a linear relationship between the rate of contamination of egg contents and the prevalence of infected laying hens in a flock, with eggshell contamination occurring at a much higher rate than that of egg contents (Arnold et al, 2014a).…”
Section: Salmonella Prevalence and Serovar Distribution Among Isolatementioning
confidence: 99%